Effect of Ambient Temperature on the Performance of PVT System in Bangladesh - Farzana, Q.; Akter, M. Sharmin; Zohora, F. T. (European Journal of Applied Sciences, 2022)
The ambient temperature has a significant impact on PVT effectiveness. In this study, the effect of ambient temperature on PVT system under specific operating conditions in Bangladesh is investigated numerically. Using the FEM, a mathematical model of a three-dimensional PVT system is taken into account and resolved. Based on Bangladesh's weather, a range of 10 to 40 degrees Celsius is chosen as the ambient temperature. It is investigated how ambient temperature affects the cell and output fluid temperatures, electrical power and thermal energy, electrical efficiency-thermal efficiency, and overall system efficiency. The calculations reveal that for every 10°C increase in ambient temperature, the cell and output water temperatures rise by 1.5°C and 0.04°C, respectively, while the electrical efficiency falls by around 0.1% and the thermal energy increases by 8.9 W.